Sclerema Neonatorum in a Term Infant: A Case Report and Literature Review - Gloria Nakalema; Walufu Ivan Egesa; Patrick Kumbowi Kumbakulu; Martin Nduwimana; Amnia Diaz Anaya; Mirembe Stephen Kizito; Daniel Kavuma (Case Reports in Pediatrics)
Sclerema neonatorum (SN) is a rare form of panniculitides with an obscure incidence, aetiology, and pathogenesis. This condition is peculiar to preterm neonates, especially those with comorbidities such as sepsis, congenital anomalies, congenital heart disease, and gastrointestinal and respiratory diseases. Usually, it presents within the first seven days of life, but may develop a few weeks later. Typically, SN manifests with diffuse hardening of the skin and subcutaneous tissues that subsequently bind to the underlying muscle and bone, often beginning in the buttocks, thighs, or trunk, and progressing to other body parts, but sparing the soles, palms, and genitalia. Diagnosis is based on clinical characteristics. It has been associated with a high mortality, despite aggressive use of various treatment modalities such as antibiotics, steroids, fresh blood transfusion, exchange blood transfusion, and intravenous immunoglobins. This is a report of a macrosomic term neonate who presented with typical clinical and histopathological features of SN.